Foreign Policy and Security: The Role of Political Parties in Responding to World Geopolitical Developments - Nurdin, Iing (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to analyze the role of political parties in formulating foreign and security policies, especially in responding to world geopolitical developments. Dynamic global geopolitical changes demand a strategic response from the state, where political parties play a key role in determining policy direction. Using a descriptive qualitative approach, this study explores data through in-depth interviews with political actors, political observers, and diplomats, as well as analysis of related documents. The results of this study indicate that political parties play an important role in formulating foreign and national security policies, especially in facing the ever-evolving dynamics of world geopolitics. Although political parties play an active role in the legislative and executive processes, the major challenges faced are differences in ideology between parties, pressure from domestic interest groups, and limited capacity of human resources with expertise in international relations and security. To overcome these challenges, it is important for political parties to improve the competence of their members through training, cooperation with experts, and maintaining domestic consensus so that foreign and security policies remain focused on national interests, stability, and the welfare of the people. The conclusion of this study confirms that political parties have a significant influence in determining foreign policies that are adaptive and responsive to geopolitical dynamics. This research provides practical implications for policy makers to strengthen the role of political parties in facing global challenges as well as theoretical contributions to the literature on international relations and domestic politics.